Persistent humoral immune response in youth throughout the COVID-19 pandemic: prospective school-based cohort study - Alessia Raineri; Thomas Radtke; Sonja Rueegg; Sarah R. Haile; Dominik Menges; Tala Ballouz; Agne Ulyte; Jan Fehr; Daniel L. Cornejo; Giuseppe Pantaleo; Céline Pellaton; Craig Fenwick; et al. (Nature Communications, 2023)
Abstract Understanding the development of humoral immune responses of children and adolescents to SARS-CoV-2 is essential for designing effective public health measures. Here we examine the changes of humoral immune response in school-aged children and adolescents during the COVID-19 pandemic (June 2020 to July 2022), with a specific interest in the Omicron variant (beginning of 2022). In our study “Ciao Corona”, we assess in each of the five testing rounds between 1874 and 2500 children and adolescents from 55 schools in the canton of Zurich with a particular focus on a longitudinal cohort (n=751). By July 2022, 96.9% (95% credible interval 95.3–98.1%) of children and adolescents have SARS-CoV-2 anti-spike IgG (S-IgG) antibodies. Those with hybrid immunity or vaccination have higher S-IgG titres and stronger neutralising responses against Wildtype, Delta and Omicron BA.1 variants compared to those infected but unvaccinated. S-IgG persist over 18 months in 93% of children and adolescents. During the study period one adolescent was hospitalised for less than 24 hours possibly related to an acute SARS-CoV-2 infection. These findings show that the Omicron wave and the rollout of vaccines boosted S-IgG titres and neutralising capacity. Trial registration number: NCT04448717. https://clinicaltrials.gov/ct2/show/NCT04448717 .